Effective Treatment of Acute Promyelocytic Leukemia With All-Trans-Retinoic Acid, Arsenic Trioxide, and Gemtuzumab Ozogamicin - Ravandi, Farhad (J Clin Oncol, 2009)
PURPOSE: We examined the outcome of patients with newly diagnosed acute promyelocytic leukemia (APL) treated with all-trans-retinoic acid (ATRA) and arsenic trioxide (ATO) with or without gemtuzumab ozogamicin (GO) but without traditional cytotoxic chemotherapy. PATIENTS AND METHODS: From February 2002 to March 2008, 82 patients with APL were treated with a combination of ATRA plus ATO. The first cohort of 65 patients received ATRA and ATO (beginning on day 10 of ATRA). High-risk patients (WBCs ≥ 10 × 10(9)/L) received GO on the first day. From July 2007, the second cohort of 17 patients received ATRA and ATO concomitantly on day 1. They also received GO on day 1, if high risk, and if their WBC increased to more than 30 × 10(9)/L during induction. Monitoring for PML-RARA fusion gene was conducted after induction and throughout consolidation and follow-up. RESULTS: Overall, 74 patients achieved complete remission (CR) and one achieved CR without full platelet recovery after the induction, for a response rate of 92%. Seven patients died at a median of 4 days (range, 1 to 24 days) after inclusion in the study from disease-related complications. The median follow-up is 99 weeks (range, 2 to 282 weeks). Among the responding patients, three experienced relapse at 39, 52, and 53 weeks. Three patients died after being in CR for 14, 21, and 71 weeks, all from a second malignancy. The estimated 3-year survival rate is 85%. CONCLUSION: The combination of ATRA and ATO (with or without GO) as initial therapy for APL was effective and safe and can substitute chemotherapy-containing regimens.